A dupla carreira do estudante-atleta: as estratégias de conciliação das rotinas no esporte e na escola - Melo, Leonardo Bernades Silva de (2018)
The dual career is a subject widely covered in the international literature and national surveys begin to present interesting results in the fields of education and physical education. We can define the dual career as a kind of formation in two agencies that generate demands and have obligations to fulfill. This thesis demonstrates how the objective management of the dual career builds a bias towards the flexibility of the school curriculum, making the dual career mediation programs alleviate the problems related to the routines, but do not find the right solutions. It may be suggested that this thesis articulates the idea that the advantages offered by the European dual career mediation programs focus on reducing the student-athlete's travel time and the compatibility of schedules, providing conditions for training and schooling to take place almost in the same space. This thesis therefore presents the advantages and disadvantages of dual career mediation programs; also an average model of conciliation of the dual career in Brazil, based on the study of student-athletes practicing football in clubs in Rio de Janeiro; and a program, which we may adopt as a national trial for dual career mediation, which is the Federal Government's Athlete Scholarship Program. What may support the thesis that dual career mediation programs are lessening the effects of this relationship, but do not present concrete solutions to this type of training, is that in the subsequent studies presented in the thesis it is shown that, even in the absence of mediation programs in Brazil, studentathletes report the same problems as in European cases. Thus, this thesis brings out the need for greater investments in understanding the context of choosing a dual career. We have seen that even with intervention at different levels, the European market is able to soften few effects of the dual career, but it does not solve the major problems that lead student-athletes to give up sports or school.